One Health approach investigating Shiga toxin-producing Escherichia coli serotypes from human stool specimens and cattle run-off water samples in South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2024)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2023.